+0

# Help. ​

+1
90
2
+1159

Help.

NotSoSmart  Sep 18, 2017
Sort:

#1
0

Evaluate abs(-4 b - 8) + abs(-b^2 - 1) + 2 b^3 where b = -2:
abs(-4 b - 8) + abs(-b^2 - 1) + 2 b^3 = abs(-4 (-2) - 8) + abs(-1 - (-2)^2) + (-2)^3×2

(-2)^2 = 4:
abs(-4 (-2) - 8) + abs(-4 - 1) + 2×(-2)^3

-4 (-2) = 8:
abs(8 - 8) + abs(-4 - 1) + 2×(-2)^3

8 - 8 = 0:
abs(0) + abs(-1 - 4) + 2×(-2)^3

-1 - 4 = -5:
abs(0) + abs(-5) + 2×(-2)^3

(-2)^3 = (-1)^3×2^3 = -2^3:
abs(0) + abs(-5) + 2×-2^3

2^3 = 2×2^2:
abs(0) + abs(-5) + 2 (-2×2^2)

2^2 = 4:
abs(0) + abs(-5) + 2 (-2×4)

2×4 = 8:
abs(0) + abs(-5) + 2 (-8)

Since 0 is at the origin, then abs(0) = 0:
abs(-5) - 8×2

Since -5<=0, then abs(-5) = 5:
5 - 8×2

2 (-8) = -16:
-16 + 5

5 - 16 = -11

Guest Sep 18, 2017
#2
0

that's alot of numbers

Guest Sep 19, 2017

### 12 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details